Analysis of the Sensitivity of the SW-420 Vibration Sensor to Minor Mechanical Disturbances in the Safe Security System - Putri, Naila Cahaya; Tasmi; Teary, Muhammad Gald (JITTER: Jurnal Ilmiah Teknologi dan Komputer, 2025)
Abstract The security of assets in closed storage such as safes faces challenges in the form of illegal unit removal and physical manipulation. This study aimed to design and evaluate an anti-theft alarm system based on the Arduino Uno microcontroller with an SW-420 vibration sensor. The approach used was a laboratory experimental method focusing on testing the system's responsiveness to low-intensity mechanical interference or "Level Easy". The results showed that the integration of the SW-420 sensor, relay module, and buzzer successfully detected physical anomalies in real-time with a response time of less than one second. The implementation of the pulseIn() function in the programming logic proved effective in processing digital vibration signals into accurate alarm activation instructions. Threshold adjustments via potentiometers and the application of debouncing methods successfully minimized the potential for false alarms. In conclusion, this prototype demonstrated high reliability as an independent and portable early warning system for the protection of static assets.  Keywords : Arduino Uno, SW-420 Sensor, Safe Security, Vibration.